2015
DOI: 10.3233/thc-151000
|View full text |Cite
|
Sign up to set email alerts
|

Design study of dedicated brain PET with polyhedron geometry

Abstract: Abstract. BACKGROUND: Despite being the conventional choice, whole body PET cameras with a 76 cm diameter ring are not the optimal means of human brain imaging. OBJECTIVE: In fact, a dedicated brain PET with a better geometrical structure has the potential to achieve a higher sensitivity, a higher signal-to-noise ratio, and a better imaging performance. METHODS: In this study, a polyhedron geometrical dedicated brain PET (a dodecahedron design) is compared to three other candidates via their geometrical effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…where Rect(F) is a rectangular profile with width F and Gauss(F) is a Gaussian profile with FWHM F. The positron range produces a non-Gaussian blurring, but for 18 F-labeled tracers imaged with this kind of scanner, its contribution to the final resolution is very small, and a rough Gaussian approximation (0.6 mm FWHM) is used here. We report the radial and tangential spatial resolutions from the center of the field of view to a 15 cm radial offset from the center of the field of view using equation (5).…”
Section: Spatial Resolution-analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where Rect(F) is a rectangular profile with width F and Gauss(F) is a Gaussian profile with FWHM F. The positron range produces a non-Gaussian blurring, but for 18 F-labeled tracers imaged with this kind of scanner, its contribution to the final resolution is very small, and a rough Gaussian approximation (0.6 mm FWHM) is used here. We report the radial and tangential spatial resolutions from the center of the field of view to a 15 cm radial offset from the center of the field of view using equation (5).…”
Section: Spatial Resolution-analytical Methodsmentioning
confidence: 99%
“…This scanner was shown via simulation to reach a sensitivity of 23% in the brain region and a CTR of better than 150 ps. Other designs focused on high sensitivity and tight enclosure include the compact, multi-layer design of Gong et al [14]; the wearable HelmetPET proposed by Majewski et al [15]; the spherical brain PET scanner proposed for compatibility with 7T MRI by Catana [16]; the tight, asymmetric cylinder brain PET scanner proposed by Wang et al [17]; and the polyhedral brain PET scanners proposed by Shi et al [18] and Tao et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al investigated several polyhedron geometries and concluded that the dodecahedron design provides the same solid-angle coverage as a spherical cap, both substantially higher than that of a 30-cmdiameter cylindrical scanner. They also claimed that the dodecahedral geometry provides the best tradeoff between solid-angle coverage and reasonable complexity to allow manufacturing and even proposed a light-sharing scheme for reading out the pentagon-shaped detectors using photomultiplier tubes (34). Subsequently, they performed careful Monte Carlo simulations for the dodecahedral geometry (Fig.…”
Section: Unconventional Scanner Geometry Conceptsmentioning
confidence: 99%
“…[86] The idea of using this kind of geometry on a radiation detector has already been considered by other groups. On [87] the authors propose a brain PET design based on a dodecahedron. On [88] the authors propose a coded spherical configuration, with 4 isotropic field of view that can be used for coded aperture and Compton imaging.…”
Section: Geometrical Considerations and Configurationmentioning
confidence: 99%